A Single‐Atom Fe‐N‐C Catalyst with Ultrahigh Utilization of Active Sites for Efficient Oxygen Reduction. Issue 30 (5th July 2022) - Ao, Xiang; Ding, Yong; Nam, Gyutae; Soule, Luke; Jing, Panpan; Zhao, Bote; Hwang, Jee Youn; Jang, Ji‐Hoon; Wang, Chundong; Liu, Meilin
Abstract: Fe‐N‐C single‐atom catalysts (SACs) are emerging as a promising class of electrocatalysts for the oxygen reduction reaction (ORR) to replace Pt‐based catalysts. However, due to the limited loading of Fe for SACs and the inaccessibility of internal active sites, only a small portion of the sites near the external surface are able to contribute to the ORR activity. Here, this work reports a metal–organic framework‐derived Fe‐N‐C SAC with a hierarchically porous and concave nanoarchitecture prepared through a facile but effective strategy, which exhibits superior electrocatalytic ORR activity with a half‐wave potential of 0.926 V (vs RHE) in alkaline media and 0.8 V (vs RHE) in acidic media while maintaining excellent stability. The superior ORR activity of the as‐designed catalyst stems from the unique architecture, where the hierarchically porous architecture contains micropores as Fe SAC anchoring sites, meso‐/macro‐pores as accessible channels, and concave shell for increasing external surface area. The unique architecture has dramatically enhanced the utilization of previously blocked internal active sites, as confirmed by a high turnover frequency of 3.37 s −1 and operando X‐ray absorption spectroscopy analysis with a distinct shift of adsorption edge. Abstract : A facile and controllable etching method is developed for the synthesis of a single‐atom catalyst with a hierarchically porous and concave nanoarchitecture for the oxygen reduction reaction. The unique structure could increase the external surface area and facilitate mass transport to internal active sites, dramatically enhancing the utilization of usually blocked single‐atom active sites.